To obtain the rule that defines the function given, we will follow the steps below:
For the first function
Step 1:
Obtain the coordinates of the line on the left-hand side of the graph
The coordinates are: (-1,4) and (-2,3)
Step 2: Get the equation of the line
![(y-4)/(x+1)=(3-4)/(-2+1)](https://img.qammunity.org/2023/formulas/mathematics/college/bwpq4wgab4nj8t2s9pabjgkb44gydhyar8.png)
=>
![\begin{gathered} (y-4)/(x+1)=(-1)/(-1) \\ \\ (y-4)/(x+1)=1 \\ \\ y-4=x+1 \\ y=x+5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yg0estb4rcg1w5a2ya4shw4o2vq4z99t83.png)
Hence the equation of the line given is
![y=x+5\text{ for the range x}\leq-1](https://img.qammunity.org/2023/formulas/mathematics/college/m86o71jle54rf9iwj7gtkzaa3gnwjfcf75.png)
Step 3: Get the equation of the second line on the graph
![y=2](https://img.qammunity.org/2023/formulas/mathematics/college/qnigwn4qimkv1jqiimwsqzjpnbrgi3na3e.png)
Hence, the equation of the line is
![y=2\text{ for the range x>1}](https://img.qammunity.org/2023/formulas/mathematics/college/fputu51fnh7sv2tvvm8ycte15yvwzozpwe.png)
Therefore, the rule that defines the function is:
![f(x)=\begin{cases}x+5\text{ for x}\leq-1 \\ -2\text{ for x>1}\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/p8wr7nbavqtitvmcgvkrzqdjlhgz2s0tvp.png)